Modus Operandi Kejahatan Pencurian Motor di Kota Kupang dan Pola Penanggulangannya : (Studi Kasus Polsek Kelapa Lima) - Maurius Septianto; Orpa Ganefo Manuain; Bhisa Vitus Wilhelmus (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The purpose of this research is to analyze the modus operandi of motorcycle theft crime in Kupang City and its prevention pattern (case study of Kelapa Lima Police Station). This research is an empirical legal research that directly observes the research location to find out the facts that occur in the field. The research data sources are primary data and secondary data which are then analyzed descriptively qualitatively. The results showed that the modus operandi of overcoming the crime of theft of motorized vehicles in the jurisdiction of the Kelapa Lima Police was iron scissors, using kunji t, using fake contact kunji, using leasing services (debtcolletor). Of all the cases of crime modus operandi of motorcycle theft above has 40 cases of different types of modes. Countermeasures carried out by law enforcement or police officers include pre-emtif efforts, which are initial efforts made by the police to prevent crime by instilling good values and norms so that these norms are internalized in each person. Preventive, These preventive efforts are a follow-up to pre-emtif efforts which are still in the prevention stage before the crime occurs. Preventive efforts that are emphasized are eliminating opportunities to commit crimes. Repressive, The countermeasures taken are by taking action against the perpetrators of crime in accordance with their actions and correcting them so that they realize that their actions are unlawful and detrimental to society.